PENGEMBANGAN APLIKASI ANDROID SIMIPA MODUL DOSEN MENGGUNAKAN METODE SCRUM - Fergie Nando Dwi Putra; Ardiansyah Ardiansyah; Dwi Sakethi; Anie Rose Irawati (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The use of mobile-based technology is very useful for all fields, especially education. The rapid development of mobile technology encourages the University to be able to take full advantage of mobile technology. The Faculty of Mathematics and Natural Sciences, University of Lampung currently only has a web-based information system and does not yet have a mobile-based application that can be used to help the learning process, so that problems often occur during the learning process. Problems that often occur are forgetting class schedules, forgetting to attend student seminars, forgetting if there is a guidance schedule, not knowing the progress of guidance student studies, etc., with the development of the SIMIPA application it is hoped that it can help overcome problems that often occur in the learning process. This development focuses on the lecturer module with features such as schedule, agenda, academic calendar, endorsements, and notifications. The method used in the development of SIMIPA is the scrum method. The Scrum method has a product backlog that is divided into eight sprints and must be worked out to meet all application requirements. The Scrum method has three roles at the time of its work, namely the product owner, the Scrum master, and the development team. The scrum method has 4 stages starting from sprint planning, daily scrum, sprint review, and sprint retrospective. The result of this research is the successful development of the SIMIPA application for the Android-based lecturer module. For testing application functionality, the black box testing method is used. The results of the black box testing on the lecturer module SIMIPA application show all functionality in the application is running and as previously expected. Keywords: Black box testing; Lecturers; Mobile technology; Notifications; Scrum